Competing Visions of Political Community in the Middle East:: The Kurdish Model as an Alternative to Theocracy and Nationalism - Baris, Hanifi (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
Democratic Confederalism, the model of political community developed by the dominant Kurdish political movements in Northern and Western Kurdistan (Turkey and Syria), is not only a model for the recognition of Kurdish national rights, autonomy or self-government. It is but an ambitious and comprehensive model of political community that has become a competitor to the three dominant visions of political community in the Middle East, namely nationalism, Islamism and (neo)Ottomanism. The model is designed to primarily tackle political domination, although it also addresses social and gender inequality, economic exploitation, environmental degradation and climate change. It therefore gets into direct confrontation with the existing political establishments in Turkey and Syria in particular and in the Middle East in general. Additionally, since the Kurdish political movement tries to realise its program without authorization from nation-states, their agenda and praxis are not tolerated by established orders and confronted violently in the region. Their program is perceived as a threat to the national security of the states involved. Hence, I argue, it is ultimately up to a Kurdish act of foundation whether the model will survive the current hostility and emerge either victorious or as an alternative to the existing models.